Ablation and thermo-mechanical investigation of polyarylacetylene impregnated heat vulcanising silicone rubber for ultrahigh temperature applications. (28th May 2018) - Liu, Y.; Ma, C.; Li, Y.; Yin, Z.; Su, J.; Gao, J.
ABSTRACT: Hot vulcanised silicone rubber composites filled with polyarylacetylene (PAA) prepolymer or carbon fibre (CFs) are prepared. The residual weight, mechanical properties and ablation property of the composite are tested. The results show that the incorporation of PAA into silicon rubber can obviously increase the residual weight of the resulting composite. The addition of PAA or CFs has improved the hardness of the composites. The tensile stress and elongation at break of the composite are found increased initially and then decreased with the increasing of the concentration of PAA. PAA and CFs can greatly improve the ablation properties of the composites. The ablated surface contains SiO2, SiC and/or Si, which hinder the oxygen diffusion and the thermal conduction, and consequently prevent the decomposition and oxidation of the composite. The crack is a crucial factor determining the thermal conduction of the ablation layer when exposed to the oxyacetylene torch.